2011
DOI: 10.1007/s12011-011-8984-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Essential Trace and Toxic Elements in Scalp Hair Samples of Smokers and Alcohol User Hypertensive Patients

Abstract: The incidence of hypertension has been associated to cigarette smoking and consumption of alcohol. In the present study, trace and toxic elements were determined in scalp hair of patients diagnosed with hypertension who are smokers and habitual alcohol drinkers living in Dublin, Ireland. These results were compared with age-and sex-matched healthy, nonsmokers, nondrinking controls. The concentrations of trace and toxic elements were measured by inductively coupled plasma atomic emission spectrophotometer after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Analysis of hair as alternative material has shown higher concentrations of necessary and toxic elements than reported in the references, even though these values vary among research papers (Chojnacka et al 2006 ; Guo et al 2007 ; Pasha et al 2007 , 2010 ; Afridi et al 2011 ; Blaurock-Busch et al 2014 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Analysis of hair as alternative material has shown higher concentrations of necessary and toxic elements than reported in the references, even though these values vary among research papers (Chojnacka et al 2006 ; Guo et al 2007 ; Pasha et al 2007 , 2010 ; Afridi et al 2011 ; Blaurock-Busch et al 2014 ).…”
Section: Discussionmentioning
confidence: 93%
“…Results obtained by Åkesson et al ( 2008 ) confirmed the hypothesis that cadmium may affect estrogen levels and thus increase the risk of hormone-dependent cancers. Smokers and people living in polluted areas have higher blood and urine cadmium levels, with smoking making the level of this element many times higher than in non-addicted individuals (Afridi et al 2011 ). Studies have confirmed that drinking alcohol in combination with smoking leads to increased absorption and accumulation of cadmium in all body tissues (Afridi et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lead is a highly toxic metal that can accumulate in the body and damage many organs and systems. It is considered a mutagenic element, among other reasons due to its lipid peroxidation enhancing effect (Afridi et al 2011 ). Lead may also be found in high concentrations in the blood and urine of smokers (Afridi et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several analytical methods like X-ray Fluorescence (XRF) [1,2], Particle Induced X-ray Emission (PIXE) [3], Neutron Activation Analysis (NAA) [4], Atomic Absorption Spectroscopy (AAS) [5], Inductively Coupled Plasma Mass Spectroscopy (ICP-AES) [6], Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-MS) [7], have been employed to identify and quantify trace elements in a wide variety of samples including biological samples. Among these analytical methods, AAS, ICP-AES, ICP-MS are routinely used for the analysis of samples in a destructive way for which the analyte should be in the form of liquid.…”
Section: Introductionmentioning
confidence: 99%